A Bibliometric Analysis of Conventional and Green Bond Research (2016–2024): Trends, Influential Contributions, and Thematic Evolution - Lama, Prashansa; Shrestha, Babita; Tumsa, Numa; Shrestha, Ashika; Bista, Soni; Maharjan, Dharma (Academia Journal of Research and Innovation, 2025)
Background: Bond markets have evolved significantly with the rise of green finance, creating parallel trajectories in research on conventional and green bonds. Understanding their academic progression is essential for recognizing knowledge gaps, thematic trends and leading contributors.Methods: A twin- track bibliometric analysis was conducted using data retrieved from Dimension AI database. Vos viewer was applied to map citation networks. Organizational influence, country-level contributions, and thematic development across both domains.Results: Green bond research has demonstrated rapid growth in citations and publication volume, outpacing conventional bond literature. Distinct high – impact papers, institutions, and contributing countries were identified in each category. Green bond studies predominantly address sustainability and policy innovation, while conventional bond research remains centered on financial markets and risk management.Conclusion: Green bonds have emerged as a dominant topic in academic figures, surpassing conventional bonds in scholarly attention band thematic breath. Distinct citation networks and thematic focuses underscore the maturing identify of green bond research. Novelty: This is the first comparative bibliometric study explicitly contrasting conventional and green bonds, providing new knowledge into their scholarly evolution and offering a structured foundation for future financial research.